Association between aggregative adherence fimbriae types including putative new variants and virulence‐related genes and clump formation among aggR‐positive Escherichia coli strains isolated in Thailand and Japan. (August 2014) - Ito, Kenitiro; Matsushita, Shigeru; Yamazaki, Mitsugu; Moriya, Kazuo; Kurazono, Takayuki; Hiruta, Noriaki; Narimatsu, Hiroshi; Ueno, Nobuhiro; Isobe, Junko; Yatsuyanagi, Jun; Kumagai, Norimichi; Hashimoto, Michiko; et al.
Abstract Enteroaggregative Escherichia coli (EAggEC) are an important cause of diarrhea. Four types of AAF have been identified; however, their prevalence and association with virulence properties remain unclear. E. coli strains carrying the aggR gene as EAggEC that were isolated in Japan and Thailand (n = 90) were examined for AAF subunit genes, two toxin genes (pet/astA), and clump formation. The most prevalent AAF gene was hdaA (28%), followed by aafA (20%), aggA (12%), and agg3A (4%), as well as a putative new AAF sequence (25.6%). Retention status of the toxin genes and intensities of clump formation appeared to vary according to the AAF type.